Temperature Measurement System Using Arduino - Yusfrizal, Yusfrizal; Mutiara Sovina; Harahap, Faisal Amir; Ivi Lazuly (Yayasan Kita Menulis, 2023)
Living things need the right temperature to meet their life needs. It is necessary to do the measurement process. One process formeasuring room temperature that is widely used at this time is the automatic temperature measurement and air conditioning system. The temperature measurement system and air conditioning automation is a system that is very useful for human life. With this system is expected to make it easier to know the room temperature. LM35 is a sensor used in this study as a sensor that is very sensitive to temperature. The sensor results are processed by Arduino Uno which is then displayed in a desktop application using C# .Net and stored in the database. The room temperature measurement system, especially the one made in this project, can measure room temperature with an unstored data tolerance value ± 4 times in one minute. When the temperature exceeds the set temperature, the fan will rotate automatically as an air conditioner. This system works every second and displays the results on the desktop application and stores them in the database as the final storage place which can be developed or made a decision in the future.